2018
DOI: 10.1016/j.dib.2018.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Data on the removal of heavy metals from aqueous solution by adsorption using melanin nanopigment obtained from marine source: Pseudomonas stutzeri

Abstract: Heavy metals are one of deadly contaminants in ground water across the globe. Thus, herein, this data set comprises experimental and modelled data on the removal of heavy metals from ground water using melanin synthesized by the marine bacteria Pseudomonas stutzeri. Characterization of biosynthesized melanin and modelling of the kinetic and the thermodynamic study on adsorption of heavy metals such as mercury (Hg(II)), lead (Pb(II)), chromium (Cr(VI)), and copper (Cu(II)) are included in this article. Apart fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…IR spectroscopy, [ 213,227 ] often FTIR spectroscopy relies on spectral differences for IR transmission (passing through samples), absorbance or reflection, where these differences enable functional group identification based on the energies of specific vibrational modes. FTIR is a very popular method of characterising melanins due to its simplicity, availability, and broad applicability, and has been used to characterize synthetic melanins (formed with a variety of monomers including dopamine, [ 228,229 ] 5‐S‐cys‐DOPA, [ 230 ] DHN, [ 231 ] and HGA; [ 232 ] and optionally the presence of additives such as anionic polysaccharides [ 134 ] to mimic the biological milieu) and natural melanins from bacteria (e.g., Pseudomonas sp ., [ 233 ] Pseudomonas stutzeri , [ 234 ] Streptomyces cyaneofuscatus [ 182 ] ), fungi (e.g., Inonotus hispidus , [ 183 ] Lasiodiplodia theobromae , [ 235 ] Yarrowia lipolytica [ 236 ] ), cuttlefish ( Sepia officinalis [ 110,237,238 ] ) and humans (e.g., kidney and prostate stones, [ 239 ] Egyptian mummies from 1500 B.C. [ 240 ] ).…”
Section: Analysis Of Melaninsmentioning
confidence: 99%
See 3 more Smart Citations
“…IR spectroscopy, [ 213,227 ] often FTIR spectroscopy relies on spectral differences for IR transmission (passing through samples), absorbance or reflection, where these differences enable functional group identification based on the energies of specific vibrational modes. FTIR is a very popular method of characterising melanins due to its simplicity, availability, and broad applicability, and has been used to characterize synthetic melanins (formed with a variety of monomers including dopamine, [ 228,229 ] 5‐S‐cys‐DOPA, [ 230 ] DHN, [ 231 ] and HGA; [ 232 ] and optionally the presence of additives such as anionic polysaccharides [ 134 ] to mimic the biological milieu) and natural melanins from bacteria (e.g., Pseudomonas sp ., [ 233 ] Pseudomonas stutzeri , [ 234 ] Streptomyces cyaneofuscatus [ 182 ] ), fungi (e.g., Inonotus hispidus , [ 183 ] Lasiodiplodia theobromae , [ 235 ] Yarrowia lipolytica [ 236 ] ), cuttlefish ( Sepia officinalis [ 110,237,238 ] ) and humans (e.g., kidney and prostate stones, [ 239 ] Egyptian mummies from 1500 B.C. [ 240 ] ).…”
Section: Analysis Of Melaninsmentioning
confidence: 99%
“…XPS involves irradiating samples with X‐rays and measuring the kinetic energy and number of electrons emitted, yielding spectra that offer insight into chemical composition (formula) and the chemical/electronic state of the elements [ 161,345 ] XPS has been applied for a variety of different melanins and reasons, showing the presence of eumelanin in cephalopod ink sacs from the Jurassic era (>160 million years ago), highlighting the potential for fundamental science offering information to archaeological studies [ 187 ] and in combination with computational studies for technological applications. [ 162 ] XPS can be used to characterize and analyze the metal ion interactions with melanins, for example, metal binding by melanins produced by Pseudomonas stutzeri , [ 234 ] highlighting the potential of such natural melanins for environmental remediation and thereby both blue and gray biotechnologies. XPS has been used to study the discoloration of a model Rattan crop ( Daemonorops margaritae ) which is cultivated on a large scale in Southeast Asia, however, discoloration diminishes its economic value, and this was shown to be primarily due to the melanins produced by fungi that grow on the rattan (in this case by XPS analysis of rattan inoculated with Lasiodiplodia theobromae ), [ 235 ] which is important for green biotechnology supported economies.…”
Section: Analysis Of Melaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanin extracted from bacteria has also been reported in heavy metal treatment, prevent fouling and formation of biofilm. Manirethan et al (2018Manirethan et al ( , 2020 used the melanin pigment extracted from gram-negative bacterium P. stutzeri for the absorption of heavy metals like copper, mercury, chromium, lead, and Arsenic where the absorption may be due to the presence of the COOH, NH, phenolic OH groups where maximum efficiency was absorbed in a pH ranging from mildly acidic to neutral. As a twist Melanin impregnated with copper and iron on its surface proved to be efficient in removing arsenic by chemisorption and it was also noted that melanin exhibited thermostability up to 120 • C and showed peak absorption of arsenic at pH of 4-6 where XPS studies showed that arsenite before binding to Cu-, Fe-Impregnated melanin oxidized to arsenate and finally removing the Cu and Fe by Hcl treatment for the recycling of melanin and again impregnating it with fresh Cu and Fe element for absorption which showed 99% efficiency to 4 absorption and desorption cycles.…”
Section: Melaninmentioning
confidence: 99%